Microbial Eukaryote Diversity and Activity in the Water Column of the South China Sea Based on DNA and RNA High Throughput Sequencing - Xu, Dapeng; Li, Ran; Hu, Chen; Sun, Ping; Jiao, Nianzhi; Warren, Alan (Frontiers in Microbiology, 2017)
To study the diversity and metabolic activity of microbial eukaryotes in the water column of the South China Sea, genomic DNA and RNA were co-extracted from samples collected down to bathyal depth at two sites. V9 regions of both SSU rRNA gene and its transcript (cDNA) were amplified and sequenced using high throughput sequencing. Our study revealed: (1) DNA and RNA datasets showed significant differences in microbial eukaryote community composition, with the variability between the two datasets for the same sample exceeding that between samples within each dataset, indicating that nucleic acid source overrode environmental factors in determining the composition of microeukaryotes; (2) despite the differences in community composition between the two datasets, both DNA and RNA revealed similar depth-related distribution patterns of microbial eukaryotes; (3) using the ratio of RNA: DNA as a proxy of relative metabolic activity, a depth-related pattern was found for the relative metabolic activity of some but not all groups of microbial eukaryotes, with the highest activity for the groups with depth-related pattern usually found in the middle water layers; and (4) the presence of live and active photoautotrophic microbial eukaryotes in the deep ocean was confirmed, indicating that they play an important role in controlling the deep-sea organic carbon pool. Overall, our study sheds light on the diversity and activity of microbial eukaryotes in the water column of a tropical oligotrophic ocean and their potential contributions in the downward transportation of organic material from the surface ocean to the deep via the biological pump.